Review of the Current Advances of Silver Halides-Based Composites as Photocatalysts for the Degradation of Organic Pollutants - Abed, Hanan H.; Ammar, Saad H. (Al-Nahrain Journal for Engineering Sciences, 2025)
Industrial activities significantly affect the environment by releasing many organic pollutants, including industrial dyes, phenols and antibiotics, which produce wastewater. Effective removal of these substances from wastewater has appeared as a noticeable research field owing to its environmental significance. Exorbitant operational expenses and the potential generation of supplementary pollutants load conventional techniques like adsorption, membrane separation, and coagulation. Semiconductor-based photocatalysis has effectively degraded organic contaminants into less toxic or biodegradable compounds. The construction of robust visible-light-sensitive photocatalytic hybrids for environmental decontamination is an inspiring task for researchers. The exceptional photocatalytic performance of silver halides (AgX, where X is I, Cl, and Br) has recently attracted significant consideration as photocatalysts. Moreover, the combination of silver halides with other photo-active semiconductors to create efficient visible-light-driven photocatalyst heterojunctions has significantly promoted the broader application of the photocatalysis process with enhanced efficiency. Ag-silver halides/semiconductors heterojunctions have developed as crucial components in efficient composites for photocatalysis through surface plasmonic actions, helping with visible light absorption. The current study overviews the most recent Ag and silver halide-based composite photocatalysts. Additionally, it provides an essential understanding of their promoted photocatalytic performances and their main applications in organic pollutant degradation. Moreover, the photocatalytic mechanisms and environmental applications of AgI and composites were discussed.